Best weight to market hogs? - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1986)
One of the important, recurring decisions that each hog producer must make is the weight at which to sell hogs. The decision to sell hogs may be influenced by cost and availability of feed, anticipated market hog price changes, weather conditions, overcrowding or need for facilities, or the need for cash for unpaid bills. All of these factors play an intricate role in the decision to market; however, the choice of when to sell may also influence production costs, price received, and carcass quality.; Swine Day, Manhattan, KS, November 20, 1986
Keywords: Swine day; 1986; Kansas Agricultural Experiment Station contribution; no. 87-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 507; Swine; Market; Hogs